High Performance Zn–Mn Cement Batteries for the Next Generation of Buildings - Liu, Zhaolong; Feng, Pan; Yuan, Long; Liu, Ruidan; Meng, Xiangyu; Tao, Guanghui; Chen, Jian; Guo, Zaiping; Miao, Changwen (Nano-Micro Letters, 2026)
Integrating energy storage into buildings through cement-based structural batteries offers a transformative pathway toward net-zero energy infrastructure. However, current cementitious structural batteries remain hampered by low energy density and poor cycle stability, largely due to the presumed electrochemical inertness of cement and severe side reactions in the alkaline cementitious environment. Herein, we identify the unexplored role of cement as functional separators containing ZnSO4 + MnSO4 (Zn–Mn) electrolyte, which facilitates the MnO2 deposition on cathode during charging and enhances capacity. Continuously generated zinc sulfate hydroxide within the cement matrix acts as a proton buffer, consuming H+ generated during the electrochemical oxidation of Mn2+. This buffering prevents local acidification and sustains birnessite-MnO₂ deposition, typically hindered in conventional neutral Zn–Mn electrolytes. This discovery leads to the concept of active cementitious separators for fabricating Zn–Mn cement batteries that combine improved compressive strength ( 20 MPa) with high specific energy density (0.92 mWh cm−2 at 1.15 mW cm−2) and excellent cycling stability (99.98% capacity retention after 1000 cycles). Our findings overturn the long-standing perception of cementitious materials as merely passive electrolyte carriers, demonstrating a ten-fold increase in both energy density and cycling stability over previous cement-based batteries. Highlights: 1 Conventional cementitious materials were engineered into active cementitious separators (ACSs) that function as capacity boosters rather than passive carriers, significantly enhancing the capacity of Zn–Mn batteries. 2 Continously generated zinc sulfate hydroxide within ACSs acts as an effective proton buffer, suppressing electrolyte acidification and stabilizing birnessite-MnO2 deposition. 3 ACSs-based Zn–Mn batteries achieve a balanced integration of structural integrity and electrochemical performance, delivering a ten-fold improvement in energy density (0.92 mWh cm−2 at 1.15 mW cm−2) and exceptional cycling stability (99.98% capacity retention after 1000 cycles).